Unsteady magnetohydrodynamic mixed convection stagnation point flow of a viscoelastic fluid on a vertical surface - Kartini Ahmad,; Roslinda Nazar, (Penerbit Universiti Kebangsaan Malaysia, 2010)
In this paper, the problem of unsteady magnetohydrodynamic (MHD) viscoelastic fluid flowing towards a stagnation point on a vertical surface is studied. The temperature of the surface is assumed to vary linearly with the distance from the stagnation point. The partial differential equations which governed the flow are transformed into a system of ordinary differential equations, which are then solved numerically by an implicit finite-difference scheme known as the Keller-box method. The effects of the viscoelastic parameter K, mixed convection parameter λ, magnetic parameter M and Prandtl number Pr on the flow and heat transfer characteristics are presented in this paper. The numerical solutions obtained are uniformly valid for all dimensionless time from initial unsteady-state flow to final steady-state flow in the whole spatial region